Analisis Tingkat Kesadaran Pentingnya Literasi Keuangan dan Sikap Keuangan Terhadap Financial Self Afficacy - Siti Aliviah Hasanah; Sukiyaningsih, Tri; Kodriyah, Kodriyah (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2026)
This study aims to analyze the influence of Financial Literacy and Financial Attitude on Financial Self-Efficacy among Accounting students at Serang Raya University. The study uses a questionnaire survey method distributed to students of the 2023-2024 cohort. The results indicate that both Financial Literacy and Financial Attitude, either partially or simultaneously, have a positive and significant effect on Financial Self-Efficacy. In conclusion, an increased understanding of financial concepts and proper financial attitudes can enhance students' confidence in managing their personal finances.